Current status of transcatheter closure of patent foramen ovale - Palacios, Dr. Igor F. (Gaceta Médica de Caracas, 2020)
A patent foramen ovale (PFO) is a highly prevalent structure among the adult population. It allows the shunt of blood through the inter-atrial septum and has been associated with cryptogenic stroke, transient ischemic attack, significant right to left shunting resulting in resting and exercise-induced hypoxemia, platypnea orthodeoxia syndrome, and decompression sickness after scuba diving and migraines. Un foramen oval permeable (FOP) es una estructura altamente prevalente entre la población adulta. Permite la derivación de sangre a través del tabique interauricular y se ha asociado con accidente cerebrovascular criptogénico, ataque isquémico transitorio, derivación significativa de derecha a izquierda que resulta en hipoxemia inducida por reposo e inducida por el ejercicio, síndrome de ortodeoxia por platipnea y enfermedad por descompresión después del buceo y las migrañas.